2016
DOI: 10.1590/0102-6720201600040008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Management for Dyslipidemia in Liver Transplant Recipients

Abstract: Background: Dyslipidemia occurs in approximately 70% of all liver transplant (LT) recipients, and no prior control studies have demonstrated any dietary intervention to change it. Aim: To analyze the effects of a dietary intervention on the lipid profile of dyslipidemic LT recipients. Methods: All LT recipients with dyslipidemia on clinical follow-up were enrolled. Anthropometric evaluation, food history, body composition (bioimpedance) and assessment of basal metabolism through indirect calorimetry were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Pinto et al evaluated the effect of diet on reducing lipid pro les in 53 patients with liver transplant, and their results showed that post-transplant TC, LDL and TG pro les were signi cantly decreased by dietary intervention. The mean of each of these pro les was 160, 84.2 and 150 mg/dL for boys and 169, 95.8 and 123.5 mg/dL for girls, respectively (10).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pinto et al evaluated the effect of diet on reducing lipid pro les in 53 patients with liver transplant, and their results showed that post-transplant TC, LDL and TG pro les were signi cantly decreased by dietary intervention. The mean of each of these pro les was 160, 84.2 and 150 mg/dL for boys and 169, 95.8 and 123.5 mg/dL for girls, respectively (10).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it is essential to consider recommendations for managing lipid levels in liver transplant recipients, including considering the risk factors of CVD and the effects of immunosuppressive agents. (10) While research on post liver transplant dyslipidemia has focused on patient factors and immunosuppressive regimens, the role of liver donors in the development or prevention of this complication are not investigate properly.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors contribute to lipid alterations, such as genetic predisposition [ 44 , 45 , 46 ], dietary habits [ 51 ], and age; however, the main effect is due to immunosuppressants, which have shown intrinsic pharmacodynamic properties to cause dyslipidemia and hyperglycemia [ 52 , 53 ]. In line with these findings, serum total cholesterol concentration is higher in the first 3–6 months after transplantation, when immunosuppressants are administered at higher doses [ 54 ].…”
Section: Dyslipidemia and Atherosclerosis In Transplant Recipientsmentioning
confidence: 99%
“…In particular, atherogenic dyslipidemia is present in about 80% of kidney transplant recipients [ 4 ], 80% of heart transplant recipients [ 5 ], and 70% of liver transplant recipients [ 57 ], compared to about 30–40% of the general population [ 58 , 59 ]. These variations are due to multiple factors, such as genetic [ 60 , 61 , 62 ] and lifestyle [ 63 , 64 ] factors; however, the main role is probably played by immunosuppressants, which exert pharmacodynamic and pharmacokinetic interferences on lipid and glycemic metabolism [ 11 , 65 ]: in fact, in the first months after transplantation, during which immunosuppressants are administered at a higher dose, higher total cholesterol serum levels were found [ 66 ].…”
Section: Atherogenic Dyslipidemia and Cardiovascular Diseases In Tran...mentioning
confidence: 99%